The survivors [compact disc, unabridged] - Harper, Jane (Jane Elizabeth) (Macmillan Audio, 2021)
Haunted by guilt for a reckless and consequential mistake in his youth, Kieran returns to his coastal hometown and his struggling fishing-industry parents, before the discovery of a body on the beach reveals long-held secrets.